2002
DOI: 10.1577/1548-8659(2002)131<0212:istsoa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Target Strength of Alewives in Freshwater

Abstract: Acoustic estimation of absolute fish abundance depends on knowledge of the relationship between target strength (TS) and size for the species of interest. We have derived a relationship between in situ TS and both length (L, cm) and mass (W, g) for alewives Alosa pseudoharengus in Lake Ontario and eight inland lakes in New York to provide equations for predicting one variable from the other. The pelagic fish community in these lakes was dominated by alewives (≥80% numerically). Target strength distributions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…Each gill-net set consisted of seven different 3-mwide 3 20-m-deep nets, each with a different mesh size (6.25, 8, 10, 12.5, 15, 18.5, and 25 mm bar measure). This set should capture alewife between 50 mm and 250 mm (Warner et al 2002). Gill-nets were set before dusk and retrieved at 02:00 h the next morning on both sampling dates.…”
Section: Derivation Of Alelux Units-ifmentioning
confidence: 99%
“…Each gill-net set consisted of seven different 3-mwide 3 20-m-deep nets, each with a different mesh size (6.25, 8, 10, 12.5, 15, 18.5, and 25 mm bar measure). This set should capture alewife between 50 mm and 250 mm (Warner et al 2002). Gill-nets were set before dusk and retrieved at 02:00 h the next morning on both sampling dates.…”
Section: Derivation Of Alelux Units-ifmentioning
confidence: 99%
“…Parkinson et al (1994) used a similar sonar to separate kokanee Oncorhynchus nerka into age-0 and age-1-3 groups in Coeur d'Alene Lake, Idaho, although differentiating between ages 1-3 required trawl samples. By use of a 70-kHz, split-beam sonar, Warner et al (2002) identified two or three sizeclasses of alewives Alosa pseudoharengus in surveys conducted in eight inland New York lakes from July through November. However, Buerkle (1987) cautioned against use of TS to differentiate lengthgroups by providing an example of TS reductions associated with increases in fish tilt rather than fish length in Atlantic cod Gadus morhua.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized equations to estimate fish lengths from TS have been developed for the side, dorsal, and any aspects (Love 1969(Love , 1971(Love , 1977. These equations are widely used, and have proven useful for a variety of species (Burczynski et al 1987;Brandt et al 1991;Yule 2000;Warner et al 2002). However, the empirical, species-specific TS-length relations more closely estimate true fish size due to the complexity of acoustic backscatter (Foote 1987;MacLennan and Simmonds 1992;Fleischer et al 1997).…”
mentioning
confidence: 99%
“…An echo integration threshold equivalent to target strength of -70 dB was applied to ABC data. Based on a target strength (TS) -length relationship for alewives (Warner et al 2002), the applied lower threshold should have allowed detection of our smallest targets of interest (≈20 -30 mm age-0 alewife). This threshold may have resulted in underestimation of rainbow smelt density because TS of age-0 rainbow smelt in August is as low as -74 dB (Rudstam et al 2003).…”
Section: Estimates Of Fish Abundance and Biomassmentioning
confidence: 99%